2010
DOI: 10.1161/atvbaha.110.213751
|View full text |Cite
|
Sign up to set email alerts
|

The Wnt Antagonist Dickkopf-1 Increases Endothelial Progenitor Cell Angiogenic Potential

Abstract: Objective-To determine the role of Wnt antagonist Dickkopf (DKK) 1 in human endothelial colony-forming cells (ECFCs) in view of the emerging importance of Wnt pathways in vascular biology. Methods and Results-Endothelial progenitor cells have been proposed to be crucial in tumor neovascularization.Recombinant DKK1 has been tested in ECFC angiogenic properties in vitro. DKK1 enhanced ECFC proliferation and the capacity of ECFCs to form pseudotubes in Matrigel. These effects have been attributed to enhancement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 27 publications
5
44
0
1
Order By: Relevance
“…Beneficial effects of anti-inflammatory agents have been reported for spinal cord injury3132, and these effects are in accordance with increased mRNA expression levels of anti-inflammatory, angiogenic, and ischemia resistance genes in CD34-positive BM cells than in CD34-negative BM cells333435363738394041. In particular, GDF15, Dkk1, IL33, and FGF9 mRNA expression levels were more than 10-fold higher in CD34-positive than in CD34-negative BM cells.…”
Section: Discussionsupporting
confidence: 60%
“…Beneficial effects of anti-inflammatory agents have been reported for spinal cord injury3132, and these effects are in accordance with increased mRNA expression levels of anti-inflammatory, angiogenic, and ischemia resistance genes in CD34-positive BM cells than in CD34-negative BM cells333435363738394041. In particular, GDF15, Dkk1, IL33, and FGF9 mRNA expression levels were more than 10-fold higher in CD34-positive than in CD34-negative BM cells.…”
Section: Discussionsupporting
confidence: 60%
“…The discrepancy between glioma tumor results and our B16F10 tumor data may be explained by the complexity of Wnt signaling components and different DKK1 delivery methods. Some papers suggest that blocking Wnt signaling induces angiogenesis [33, 34]. Other papers demonstrated that Wnts, including Wnt3a and Wnt5a, stimulate proliferation and enhance tube formation of cultured human ECs [5, 3537].…”
Section: Discussionmentioning
confidence: 99%
“…In a pregnant mouse model, DKK1 was highly expressed in the maternal decidual compartment, a culture of decidual cells in the presence of antisense DKK1 decreased trophoblast invasiveness, and treatment with antisense b-catenin increased trophoblast attachment and invasiveness, suggesting that an increase in WNT signaling may prevent decidualization and trophoblast cell invasion [70]. The inhibitive role of WNT signaling on vascularization in association with decreased DKK1 has been shown in cases of diabetic retinopathy [71], in human umbilical vein endothelial cells [72], and in human breast tumors [73]. Our data suggest that a decrease in DKK1 leading to aberrant WNT signaling results in ''fatty'' placentas with less decidual/junctional thickness and, therefore, a decrease in placental efficiency.…”
Section: Strakovsky and Panmentioning
confidence: 98%